Distribution of Helminth Parasites in Intestines and Their Seasonal Rate of Infestation in Three Freshwater Fishes of Kashmir - Asifa Wali; Masood-ul Hassan Balkhi; Rafia Maqbool; Mohammed Maqbool Darzi; Feroz Ahmad Shah; Farooz Ahmad Bhat; Bilal Ahmad Bhat (Journal of Parasitology Research)
The present study was undertaken to determine the incidence of helminth parasites in fishes with special reference to water quality parameters in Dal Lake and River Jhelum and correlate the observations. Water, fish, and parasite samples were collected during different seasons from various sites and processed. Three fish species, namely, Schizothorax niger Heckel 1838, Schizothorax esocinus Heckel 1838, and Schizothorax curvifrons Heckel 1838, were recovered from these water bodies. The physicochemical parameters temperature, dissolved oxygen, pH, and free carbon dioxide showed variation vis-à-vis the season and location of the stations in water bodies. Acanthocephalan parasite Pomphorhynchus kashmirensis Kaw 1941 (27.47%) and two intestinal cestodes Bothriocephalus acheilognathi Yamaguti 1934 (30.63%) and Adenoscolex oreini Fotedar 1958 (32.43%) were recovered from all the three species of Schizothorax. All the three parasites showed higher prevalence during summer and the least prevalence during winter. Parasitic infections were prevalent more in male fishes compared to females. The presence of the parasites had reduced the condition coefficient of the infected fishes in both water bodies. The study also showed that some of the physicochemical features showed a significant positive correlation with the prevalence.